Death Audit An Experience In Medicine Ward - Abedin, MF; Abedin, MJ; Uddin, AFMH; Mujumdar, MI; Chowdhury, RS; Saha, AK; Faiz, MA (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Recently Directorate General of Health Services provided a circular to maintain death audit in every department of health sector (Public health-2/ESD-01/ information/2008/454). Death audit is important because it gives an understanding to what happens and why. This helps to go beyond rates and ratios to determine the inciting factors and to take measures how deaths could have been avoided7. This study was designed to find out relation between some factors like age, sex, causes, diurnal variation, duration of hospital stay with death pattern in adult medicine units, in a tertiary health facility and major error in death certification as described by WHO like mechanism of death listed without an underlying cause, improper sequencing of events and competing cause of death, minor errors like abbreviation, absence of time intervals and mechanism of death followed by underlying legitimate cause of death8 . Methodology: This was a cross-sectional study carried out in medicine department of Mitford hospital, Dhaka from March 2010 to August 2010. During this period a total of 100 consecutive deaths except those who were brought dead included in this study. Death certificate play a important role to make successful death audit. Our existing death certificate which is supplied by the government of Bangladesh was not adequate enough to fulfill the format of cause of death section based on the recommendation of the World Health Organization. More over our doctor are not trained enough for appropriate fulfillment of death certificate. Major errors are mechanism of death listed without an underlying cause, Improper sequencing, Competing cause and minor errors are using abbreviations, absence of time intervals, mechanism of death followed by underlying legitimate cause of death. Definition of major & minor errors in death certificate are shown in Table(I)). Ethical clearance was obtained from the concerned authority to conduct the research work. We used purposive non probability sampling for collection of cases. Our inclusion criteria was all death during study period & exclusion criteria was Brought dead. We developed a network with nurses, internee and midlevel doctors so that one of us could reach the hospital within half an hour of a death. After taking permission from hospital authority necessary data were collected from hospital case records, admission register, case files A checklist was designed to record profile of patients, time of admission, diagnosis at the time of admission , time of death and cause of death. Data were analyzed by SPSS where necessary. Results: During the study period a total 13,123 (Male-5249, 40%; Female-7874,60%) patients were admitted in the medicine department of Sir Salimullah Medical College (SSMC) and Mitford Hospital. Among them consecutive 100 deaths in medicine ward were analyzed under death audit. Among 100 deaths 48% were male(n=48) and 52% were female(n=52). The age range was 15-85 years. The highest incidence of death occurred in 56- 65 years group. This group represents 24% of total death. Within this group 66.7%(N=16) were male and 33.3%(N=8) were female. As shown in table (II). J Bangladesh Coll Phys Surg 2014; 32: 137-141